Analyses of european cybersecurity frameworks - Yevdokymenko, M.; Sebastian Floderus; Linus Rosenholm; Vincent Tewolde (ХНУРЕ, 2020)
The main purpose of the paper is to analyze the EU cybersecurity frameworks and policies, to compare the development strategies of European countries and Ukraine, to identify compatibility and gaps between them for further developing recommendations for creating a more reliable and safe ecosystem through integrating EU cybersecurity frameworks.